(untitled) (Archives of Criminology, 2010)
The author reviews those types of prohibited acts under criminal code and petty offences code which provide for public order protection. This serves as an attempt to prove that a value like public order should rather be protected under petty offences code (or other forms of legal sanctions eg. administrative ones) rather than under criminal law. The scope of criminalisation should not be extended towards criminalisation of acts against public order. This can be summarised in a debate on forms of legal reaction to prohibited acts. The review of the relevant act of law becomes the point of departure to formulate the opinion that public order is a separate object of legal protection. It does not require penal sanctions provided for crimes – in spite of well-established opinions in legal literature that petty offences differ from crimes basically only in the degree of social damage they cause. The author also makes numerous observations of a classical penal reaction indicators which can be described as “punitive type sanctions”. This proves that our times bring an abrupt increase of legal regulations which create norms of public order and prohibit acts of administrative character which do not belong to the area of criminal law and should not require sanctions provided for acts classified as crimes. A thorough examination of types of petty offences made in the article provides a surprising picture of what the legislator included under the sphere of public order. Names of particular divisions of the code are irrelevant here. In the view of the examination of the acts prohibited by petty offences code, public order is recognised by designators, that is objects protected by particular types of acts, regardless of the title of the chapter they were placed in. They include quiet night hours, protection of plants in public green areas, lack of graffiti on buildings, freedom from aggressive prostitution offers, beggary without a substantial cause, lack of soil in public places, conducting a business without registration required by law, registration of place of residence, obeying rules on public roads, freedom from various forms of disturbance of peace and quiet, freedom from infringements of public assembly or no production of skeleton keys and seals or stamps without a licence. There is also a category of bitypical offences that is prohibited acts which are classified as a petty offence or a crime depending on the value of property (eg. theft of an item of values less than PLN 250 is a petty offence, not a crime). In the opinion of the author, if they are classified as petty offences they can also be included in the category of violation of order, although this order has more of a civil that administrative character. Separate comments concern the criteria of classification of petty offences in fiscal penal code.